PENGARUH HARGA, KUALITAS PRODUK, DAN PERMINTAAN PASAR TERHADAP PENDAPATAN PENGEPUL PORANG: Studi Di Kecamatan Saradan Kabupaten Madiun - ADE MESYA BELLANTI; TATIK MULYATI; MUHAMMAD IMRON (ITB AAS Indonesia Surakarta, 2026)
This study aims to; 1) determine the effect of price on the income of porang collectors in Saradan District, Madiun Regency; 2) determine the effect of product quality on the income of porang collectors in Saradan District, Madiun Regency; 3) determine the effect of market demand on the income of porang collectors in Saradan District, Madiun Regency; 4) determine the effect of price, product quality, and market demand simultaneously on the income of porang collectors in Saradan District, Madiun Regency. The sample required is 134 respondents using quantitative research methods. The results of the study obtained by t-test and F-test show that; 1) the price is obtained with a significant level of 0.009 <0.05 partially the price variable (X1) has a positive and significant effect on the income of porang collectors; 2) product quality is obtained with a significant level of 0.020 <0.05 partially the product quality variable (X2) has a positive and significant effect on the income of porang collectors; 3) market demand is obtained with a significant level of 0.001 < 0.05 partially the market demand variable (X3) has a positive and significant influence on the income of porang collectors. Simultaneously shows that price, product quality, and market demand are obtained with a significance level of F = 0.000 < α = 0.05 thus simultaneously the variables of price, product quality, and market demand have a positive and significant influence on the income of porang collectors.